Comparative Study on Variations of Living Standard for Public and Private University Students in Sylhet City of Bangladesh - Islam, Md. Anowarul; Biswas, Chanchal; Kabir, Md. Najmul (Papanda Publishier, 2025)
The attempt of this present research is to conduct a comparative study for estimation of socioeconomic variations in standard of living for both private and public university students in Sylhet urban area of Bangladesh. The results represent that the living standard of a private university student is significantly higher than a public university. The main reasons are that the students of private university have ability to spend more money for better university facilities including accommodation costs and for better living expenses than the public university. The amount of education costs also varies based on parent’s income and it is significantly high for private university students than public university. It founds that the engagement in extra-curricular activities of a public university student is higher than private university. It also found that the monthly expenditures of male students are significantly higher than the female students.